Chemical composition, cytotoxicity and anti-mycobacterium activities of Clausena anisata essential oils - Ibraheem O. Lawal (AOSIS, 2020)
Background: Clausena anisata (Willd) Hook has demonstrated several medicinal properties against certain bacterial infections, including tuberculosis. However, scientific validation is imperative to verify its folkloric usage against tuberculosis. Aim: This study aimed at determining the chemical composition, toxicity and anti-tubercular potentials of the oils extracted from this plant. Setting: Plant material collection, essential oils extraction and antimycobacterial activity were performed at the University of Fort Hare, Alice, South Africa. This article and selected technical aspect was constructed at the Biomedicinal Research Centre, Forestry Research Institute of Nigeria. Methods: Comparative chemical composition of hydrodistilled (HD) and solvent-free microwaved essential (SFME) oils from C. anisata was analysed by gas chromatography coupled with mass spectroscopy (GC-MS). In vitro minimum inhibitory concentration (MIC) assay was also carried out on the oils against a strain of Mycobacterium tuberculosis. The cytotoxicity assay of the oils was also assessed by using human dermal fibroplast (MRHF) cell lines. Results: Gas chromatography-mass spectroscopy analysis of the essential oils revealed 51 distinct compounds with methyl eugenol and estragole in abundance. The IC50 of volatile oils from SFME and HD methods against the MRHF cell line were 1 216 µg/mL and 383 µg/mL, respectively. On the other hand, both oils and ethambutol (standard drug) showed no activity against the strain of M. tuberculosis, but rifampicin supressed the growth of the organism at 0.25 µg/mL. Conclusion: This study showed that C. anisata is safe for consumption, and further studies of combinative potent but non-toxic oils engaging hydrodistillation method are strongly recommended for enhanced effect against M. tuberculosis.